2016
DOI: 10.1007/s13762-016-1075-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost biochar derived from herbal residue: characterization and application for ciprofloxacin adsorption

Abstract: Thermally carbonization biochar produced from a traditional Chinese herbal medicine waste (Astragalus mongholicus residue) was investigated for its performance in ciprofloxacin adsorption. Batch sorption experiments were conducted, and scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray photoelectron spectroscopy and Brunauer-Emmett-Teller surface area analyses were employed to characterize the biochar. The results demonstrated that thermal activation process improves the adsorbent cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Researchers have found that tea residues can significantly improve the soil fertility, leading to their use as organic fertilizers [ 9 ]. In addition, tea residues have been developed as a non-conventional water adsorbent to remove water pollutants like methylene blue [ 10 ], antibiotics [ 11 ], and heavy metals, such as chromium [ 12 ], cadmium [ 13 ], copper [ 14 ], lead, zinc [ 15 ], and arsenic [ 16 ] from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have found that tea residues can significantly improve the soil fertility, leading to their use as organic fertilizers [ 9 ]. In addition, tea residues have been developed as a non-conventional water adsorbent to remove water pollutants like methylene blue [ 10 ], antibiotics [ 11 ], and heavy metals, such as chromium [ 12 ], cadmium [ 13 ], copper [ 14 ], lead, zinc [ 15 ], and arsenic [ 16 ] from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21] Due to its low cost, wide range of raw material, superior surface properties and rich functional groups, biochar can be used as a potential sorbent to remove many kinds of heavy metal pollutants like Cd, As, Pb and organic pollutants in water. [22][23][24][25] Our previous study indicated that biochar produced from wheat straw had a good adsorption capacity for Cd(II). 26 The adsorption capacity and mechanisms of heavy metal by biochar could be inuenced by the physical and chemical properties of biochar determined by original feedstock and pyrolysis temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the structure of the CIP molecule, the dominated adsorption mechanism was also π-π EDA interactions. The presence of aromatic rings and electron acceptor atoms, i.e., fluorine and nitrogen, in the CIP molecule (structure shown in Table 1) is conducive to the formation of π-π EDA bonds with a BC surface rich in arene structures [135]. In relation to the adsorption of CIP and doxycycline (DOX) onto BCs produced from rice straw at various temperatures (300, 500, and 700 °C), researchers have drawn similar conclusions regarding the adsorption mechanisms (the dominance of π-π EDA bonding), and the effect of BC porosity (increasing pyrolysis temperature increases BC porosity and hence drug adsorption).…”
Section: Effect Of Pyrolysis Conditionsmentioning
confidence: 99%